Gonadal function in Hodgkin's disease: long-term follow-up of chemotherapy. Issue 6355 (4th December 1982) - Waxman, J H; Terry, Y A; Wrigley, P F; Malpas, J S; Rees, L H; Besser, G M; Lister, T A
Abstract : A long-term study of gonadal function was conducted in 46 men and 28 women in prolonged remission of advanced Hodgkin's disease after cyclical combination chemotherapy with nitrogen mustard, vinblastine, prednisolone, and procarbazine. The mean follow-up was 6.9 years. Azoospermia or profound oligospermia occurred in 36 of the men, but late recovery was occasionally observed. Testosterone secretion was preserved. Amenorrhoea and gonadal hormone deficiency developed in 22 of the women and never recovered. Partial or complete chemical sterilisation and gonadal hormone deficiency is currently a consequence of cure of advanced Hodgkin's disease in most patients.